Language as a Means of Marginalization in News Headline Discourse on Social Media - Harjanti, Fransisca Dwi; M, Lusy Tunik; Ardiansyah, Roely (NOBEL: Journal of Literature and Language Teaching, 2024)
This critical discourse study examines how language is used to marginalize certain groups in news titles published on social media. It focuses on linguistic elements, including words or terms, phrases, and sentences. As qualitative research employing discourse analysis methods, this study analyzes data from news headlines on social media or online media. Social media was chosen due to its widespread popularity as a source of information. Data analysis follows Fairclough’s theory, which includes text description, interpretation, and explanation. The findings reveal that news headlines often use words, phrases, and sentences to marginalize specific societal groups. Marginalized groups include powerful entities such as government officials accused of legal violations and marginalized individuals such as women. The language used in these headlines frequently involves negative connotations or dysphemisms, which emphasize undesirable traits or behaviors. Additionally, question sentences are employed in headlines to further marginalize these groups. This analysis highlights how linguistic choices in news titles reinforce societal biases and marginalize both dominant and disadvantaged groups.